Structural evaluation of the dome of the Tacna Cathedral and reinforcement proposal - Avendaño Jihuallanga, César José (2018)
The purpose of this research is to contribute to preservation of our historical heritage represented in this study by the Cathedral of Tacna, making an analysis of the cathedral with emphasis on the dome through a model in a specialized software, using the Finite element tool. From the structural analysis carried out, it was determined that the dome of the cathedral of Tacna would fail in several points, for which reason the respective reinforcement with the Geosteel 2000 material is proposed, whose inclusion in the model realized results in an improvement in its capacity resistant. Finally it is concluded that it is necessary to reinforce the dome and the proposed material fulfills the function of improving the resistant capacity of it.